2019
DOI: 10.3390/jcm8101657
|View full text |Cite
|
Sign up to set email alerts
|

18F–Choline PET/CT Identifies High-Grade Prostate Cancer Lesions Expressing Bone Biomarkers

Abstract: The main aim of this study was to investigate the possible association between 18F–choline uptake and histopathological features of prostate biopsies such as the Gleason Group and the expression of both epithelial to mesenchymal transition (vimentin) and bone mineralization (bone morphogenetics protein (BMP)-2, runt-related transcription factor 2 (RUNX2), receptor activator of nuclear factor-κB ligand (RANKL), vitamin D receptor (VDR), and pentraxin 3 (PTX3) in situ biomarkers. To this end, we enrolled 79 cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 40 publications
1
13
0
Order By: Relevance
“…Furthermore, the results showed that the odontogenic capacity of BMP-2 was better than that of FGF9. It is well recognized that BMP-2 is a critical growth factor and important biomarker involved in osteo/odontoblastic differentiation and bone formation [41][42][43]. Our results revealed the similar trend that BMP-2 offered a strong signal for differentiation and mineralization of hDPSCs, but was different from Lu et al [44] which indicated that exogenous FGF9 suppress osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 65%
“…Furthermore, the results showed that the odontogenic capacity of BMP-2 was better than that of FGF9. It is well recognized that BMP-2 is a critical growth factor and important biomarker involved in osteo/odontoblastic differentiation and bone formation [41][42][43]. Our results revealed the similar trend that BMP-2 offered a strong signal for differentiation and mineralization of hDPSCs, but was different from Lu et al [44] which indicated that exogenous FGF9 suppress osteogenic differentiation.…”
Section: Discussionsupporting
confidence: 65%
“…The study of the mechanisms involved in the formation of ectopic calcifications, as well as the characterization of the prognostic value of these calcium deposits, represent an intriguing challenge for biomedical research. Indeed, the presence of ectopic calcifications is considered a clinical sign of tissue degeneration in numerous human diseases such as atherosclerosis, breast cancer, prostate cancer, and neurological disorders [ 9 , 11 , 12 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of these choline-uptake functions was reported to induce apoptotic cell death [ 8 , 9 , 10 , 11 , 12 ]. PET/CT imaging using 18 F- and 11 C-choline captures a very high accumulation of choline in tumors [ 13 , 14 , 15 ]. This choline accumulation in tumors is thought to be related to increased choline uptake due to increased cell-membrane synthesis associated with active cell proliferation, which is reported in many cancers [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%